MAKNA KIASAN DALAM PIDATO ADAT MALEWAKAN GALA BATAGAK PANGHULU DI NAGARI MUARO PANEH KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Rini Wirasty B (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2021)
The background of the problem in this research is Nagari Muaro Paneh Bukit Sundi Kabupaten Solok is the background in this research people use Minangkabau language in everyday speech. Speeches containing figurative meanings contained very rarely spoken by the community, some younger generations lack the understanding of the figurative meanings contained. The custom of malala gala still gets its place in the middle of society and always done in every traditional ceremony. In addition, a small proportion of the younger generation are still willing to learn about Malewa Traditional gala. The purpose of this research is to describe the meaning in the metaphor in the text of Malewa Gala Batagak Panghulu customary speech in Nagari Muaro Paneh Bukit Sundi Kabupaten Solok. This research type is qualitative research by using descriptive method. The object of research is the text of Malewa Gala Batagak Panghulu customary speech in Nagari Muaro Paneh Bukit Sundi Kabupaten Solok. The research findings of figurative meanings are improper meanings, the language is based on figures. The figurative meaning is conveyed in the text of the Malewa tradition of Gala Batagak Panghulu. In the data that has been obtained in the research, that on the meaning of metaphor in the text of custom speech Malewa Gala Batagak Panghulu in Nagari Muaro Paneh Bukit Sundi Subdistrict Solok Regency there are 140 where there are 7 idiom data idiom meaning that is 5 full idioms and 2 partial idiom data, meaning kias phrases contain 13 which are entirely word or group of distinctive words to express something meanings with the meaning of the metaphor of data and the meaning of the maxim of the proverbs there are 120 data which 6 including the proverbial thimbles, the proverbial proverbs, the 50 proverbs, 2 proverbs of the parable, and 17 including proverbs are like. Suggested community leaders in order to preserve and socialize the values ​​contained in the figurative meaning in the text of Malewa Gala Batagak traditional speech Panghulu.